Fast Fluorescence Lifetime Imaging Reveals the Aggregation Processes of α-Synuclein and Polyglutamine in Aging Caenorhabditis elegans - Laine, Romain F. (ACS Chem Biol, 2019)
The nematode worm Caenorhabditis elegans has emerged as an important model organism in the study of the molecular mechanisms of protein misfolding diseases associated with amyloid formation because of its small size, ease of genetic manipulation, and optical transparency. Obtaining a reliable and quantitative read-out of protein aggregation in this system, however, remains a challenge. To address this problem, we here present a fast time-gated fluorescence lifetime imaging (TG-FLIM) method and show that it provides functional insights into the process of protein aggregation in living animals by enabling the rapid characterization of different types of aggregates. Specifically, in longitudinal studies of C. elegans models of Parkinson’s and Huntington’s diseases, we observed marked differences in the aggregation kinetics and the nature of the protein inclusions formed by α-synuclein and polyglutamine. In particular, we found that α-synuclein inclusions do not display amyloid-like features until late in the life of the worms, whereas polyglutamine forms amyloid characteristics rapidly in early adulthood. Furthermore, we show that the TG-FLIM method is capable of imaging live and non-anaesthetized worms moving in specially designed agarose microchambers. Taken together, our results show that the TG-FLIM method enables high-throughput functional imaging of living C. elegans that can be used to study in vivo mechanisms of protein aggregation and that has the potential to aid the search for therapeutic modifiers of protein aggregation and toxicity.